اللغات الضعيفة في المستوى النحوي دراسة وصفية معيارية - إسراء كريم صادق عبد الباحثة; مظفر عبد رومي. أ. م. د. (لارك للفلسفة واللسانيات والعلوم الاجتماعية, 2026)
ملخص البحث: يستعرض هذا البحث موضوع دراسة المستوى النحوي في اللغات الضعيفة دراسة وصفية معيارية، تُعني بتتبع وتحليل الظواهر النحوية في اللغات هذه برؤية القواعد النحوية المعتمدة عليها عند علماء اللغة. وتوضح هذه الدراسة في كل من القراءات القرآنية أو في غير القراءات من النصوص العربية، ويعزز البحث في بيان مظاهر الضعف اللغوي التي تظهر في صيغ النحو وخاصةً في صيغة الماضي، الجزم، والتعدية بالهمز. وبيان البحث كيف تؤثر هذه الظواهر على تركيب الجملة العربية ودلالة الفعل، ويتناول فيه أمثلة تطبيقية من النصوص القرآنية والنصوص التراثية في اللغة العربية التقليدية، لتوضيح الاختلافات في الأوجه الذي يحصل بين القراءات والأساليب النحوية المختلفة. كما تسعى الدارسة في هذا البحث إلى فهم اللغة الضعيفة في المستوى النحوي، ويجمع الوصف مفصل بين الظواهر النحوية اللغوية والمعيار النحوي المحدد عند النحاة، مما يُساهم في فهم أوسع لطبيعة اللغة الضعيفة. قد تبرز أهمية البحث إلى تقديم نموذج شامل لدراسة هذه الظواهر لتفسير النصوص القرآنية وتحليل واضح في البنية النحوية في بناء الجملة والفعل في اللغة العربية. Abstract: This research examines the study of the grammatical level in weak languages through a descriptive and normative approach. It focuses on tracing and analyzing grammatical phenomena in these languages by examining the grammatical rules relied upon by linguists. The study is applied to both Quranic readings and other Arabic texts, highlighting the manifestations of linguistic weakness evident in grammatical forms, particularly in the past tense, the jussive mood, and transitivity with the hamza. The research demonstrates how these phenomena affect the structure of Arabic sentences and the meaning of verbs. It includes applied examples from Quranic texts and classical Arabic texts to Illustrate the differences that arise between various readings and grammatical styles. This research aims to understand weak languages at the grammatical level, and its detailed description combines linguistic grammatical phenomena with the grammatical standards established by grammarians, thus contributing to a broader understanding of the nature of weak languages. The research’s sIgnifIcance lies in providing a comprehensive model for studying these phenomena to interpret Quranic texts and offer a clear analysis of the grammatical structure of sentences and verbs in Arabic.